Transportation-Induced Carbon Emissions Jeopardize Healthcare Logistics Sustainability: Toward a Healthier Today and a Better Tomorrow - Khalid Zaman; Muhammad Khalid Anser; Usama Awan; Wiwik Handayani; Hailan Salamun; Abdul Rashid Abdul Aziz; Mohd Khata Jabor; Kamalularifin Subari (MDPI, 2024)
Logistics 2022, 6(2), 27; https://doi.org/10.3390/logistics6020027